Universal coverage, enhancing spacecom sector growth, and supporting democratic ethos: The role of satellite spectrum assignment - Rekha Jain (Indian Council for Research on International Economic Relations (ICRIER), 2023)
Satellite communication is integral to Digital India, enabling ubiquitous broadband for the uncovered population and supporting satellite TV, the dominant source of infotainment. An enabling policy environment would help increase the market share of Indian satellite service providers from the current 2% of the global market. Satellite spectrum is a shared resource, in contrast to mobile and broadcast terrestrial services, that require exclusive assignment. It is imperative that the spectrum assignment policy leverages this aspect. This paper develops criteria for assessment of the two possible policies - exclusive assignments through auctions and shared assignments administratively. We find that the latter meets the above stated policy objectives better, is in tune with global best practices and supports multiplicity of satellite TV channels providing plurality of content, critical for a functioning democracy. It suggests an administered price model for allocation of satellite spectrum with a one-time payment of license fee and a revenue share of aggregate gross revenue, annually.
Keywords: L13; L51; L96; 330; Satellite communications; space; spectrum management; auctions